Non-small cell lung cancer treatment - Manegold, Christian; Allgayer, Heike (UNI-MED Verlag, 2013)
Intro -- Authors -- Contents -- 1. The Changing Epidemic of Lung Cancer -- 1.1. Histological variability -- 1.2. References -- 2. Establishing a Tumor Tissue Bank: An Interdisciplinary Challenge -- 2.1. Requirements for establishing and conducting a tumor tissue bank -- 2.1.1. Personnel -- 2.1.2. The structural and technical requirements -- 2.1.3. Ethics -- 2.2. Planning of the tumor bank -- 2.3. Conducting a tumor tissue bank in practice -- 2.3.1. Logistics -- 2.3.2. From surgical resection to cryopreservation -- 2.3.3. Quality control -- 2.3.4. Documentation -- 2.4. Problems and perspectives -- 2.5. References -- 3. Diagnostic Pathology and Molecular Profile of Non-Small Cell Lung Cancer -- 3.1. Highlights in diagnostic pathology: Old concepts and new requirements in NSCLC diagnosis -- 3.2. Subtypes of NSCLC -- 3.2.1. Adenocarcinoma -- 3.2.2. Squamous cell carcinoma -- 3.2.3. Large cell carcinoma and "combined" carcinoma subtypes -- 3.3. Histological subtyping of NSCLC in small biopsies and cytological samples: The role of immunohistochemistry -- 3.4. Molecular profile of NSCLC -- 3.4.1. Molecular pathology of adenocarcinoma -- 3.4.2. Molecular pathology of squamous cell carcinoma -- 3.4.3. Molecular pathology of large cell carcinoma -- 3.5. Conclusions -- 3.6. References -- 4. EGFR-Mutations in NSCLC: Strategies to Implement Routine Testing in Germany -- 4.1. Targeted therapies and biomarkers for the guidance of therapy decisions in patients with malignant tumors -- 4.2. The EGFR pathway in nonsmall cell lung cancer (NSCLC) -- 4.3. General considerations on mutation testing in routine diagnostics -- 4.4. Implementation of EGFR ring trials on NSCLC as prerequisite for reliable testing of patient material -- 4.5. Results of the first interlaboratory ring trial on EGFR mutations of NSCLC in Germany -- 4.6. Final recommendations.
Description based on publisher supplied metadata and other sources